The Effect of Immersion Time on Corrosion Rate on St37 Carbon Steel in 3% NaCl Corrosive Medium Using Waru Leaves Extract Inhibitor - Sinaga, Fredison Dian; Suka, Ediman Ginting; Karo, Pulung Karo (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
The research of effect of immersion time on the corrosion rate of St37 carbon steel has been conducted in a 3% NaCl corrosive medium using a hibiscus leaves extract inhibitor. The samples of carbon steel St37 were immersed in a corrosive medium of NaCl 3% without being given and given the inhibitor of hibiscus leaf extract with a concentration of 15% for 3, 6, 9, and 12 days. Calculation of reduction in corrosion rate is carried out by the weight loss method. The results showed that adding the hibiscus leaves extract inhibitor effectively reduced the sample's corrosion rate with the most excellent efficiency at nine days immersion, which was equal to 78,48%. The results of XRD characterization show that the phase formed is pure Fe is a corrosion product. The results of SEM characterization showed that the surface microstructure of the sample after immersion was cracks, holes, and lumps, which indicated that the sample had been corroded. The results of EDS characterization show that in the soaked sample, there were corrosion products in the form of FeO compounds whose magnitude increased with every immersion.